Quantitative measurement on coal components through the interpretation model of geophysical log: A case study from the Qaidam Basin, NW China. Issue 6 (November 2021) - Liu, Shiming; Liu, Rui; Tang, Shuheng; Zhao, Cunliang; Liu, Bangjun; Diao, Junwei; Xi, Zhaodong
The Iqe coalfield is one of the most significant coal production bases in the Qaidam Basin. Over the last few decades, core explorations have targeted the Dameigou Formation for No. 7 coal seam (M7). Although many M7 coal samples have been analyzed for coal components in the laboratory, the systematic understanding of the components and changes of coal in the whole Iqe coalfield is still inadequate. In this study, we focus on building log interpretation models to accurately calculate the content of coal components of M7, including ash yield (Aad ), volatile matter (Vdaf ), fixed carbon (FCad ), and moisture (Mad ). Multiple regression analysis and statistical method, combined with the rock volume model, were used to establish log interpretation models of coal components. A total of 28 coal samples from ZK1, ZK2, ZK11-5, ZK23-4, and ZK36-9 wells in the Iqe coalfield were involved in the modeling, as well as well-logs parameters, such as radioactivity (GR), compensation density (DEN), acoustic (AC), and resistivity (RLLD). According to sensitivity analysis, the fitted Aad and Vdaf contents of M7 increase with the increasing of DEN and GR values, whereas the FCad content shows the opposite way. Furthermore, the positive relationship between Aad and Vdaf ( R 2 = 0.59) and the negative relationship between Aad and FCad ( R 2 = 0.92) as well as Vdaf and FCad ( R 2 = 0.69) indicate that Aad is a key factor in coal and should be prior determined. Finally, based on the multiple regression analysis and rock volume model, we proposed log interpretation models for M7 coal components in the Iqe coalfield, these models have been examined successfully by the case studies from the same coalfield and will provide new insights into the application of geophysical log parameters for coal quality evaluation.